THE ILLOCUTIONARY ACTS ANALYSIS OF WILL SALAS’ UTTERANCES FROM IN TIME FILM - I Komang Muliartawan; I Gusti Ayu Vina Wiadnyana Putri (Universitas Pendidikan Ganesha, 2023)
This study focused on analyzing utterances produced by the main character of In Time film, which is Will Salas. The aim of this study is to find out the types of illocutionary acts produced by Will Salas as the main character of In Time film, using the theory that proposed by Searle (1979) which classified illocutionary into five categories, namely assertives, directives, expressives, commissives and declarations. In collecting the data in this study, observation methods were used adapted to the following steps; watching, note-taking, and classifying. The types of illocutionary acts that were found from the utterances uttered by the main character were analysed using descriptive qualitative method with these several steps; identifying, describing, analysing using Searle’s theory about illocutionary acts.The result of this study is that Will Salas produced 275 utterances and all types of illocutionary acts found in the utterances of the main character from In Time film. The most dominant types of illocutionary acts found were assertives acts and the least types of illocutionary acts found were declarations acts.